SPRYSEC Effectors: A Versatile Protein-Binding Platform to Disrupt Plant Innate Immunity - Diaz-Granados, Amalia; Petrescu, Andrei-José; Goverse, Aska; Smant, Geert (Frontiers in Plant Science, 2016)
Persistent infections by sedentary plant-parasitic nematodes are a major threat to important food crops all over the world. These round worms manipulate host plant cell morphology and physiology to establish sophisticated feeding structures. Key modifications to plant cells during their transition into feeding structures are largely attributed to the activity of effectors secreted by the nematodes. The SPRYSEC effectors were initially identified in the potato cyst nematodes Globodera rostochiensis and G. pallida, and are characterized by a single SPRY domain, a non-catalytic domain present in modular proteins with different functions. The SPRY domain is wide-spread among eukaryotes and thought to be involved in mediating protein-protein interactions. Thus far, the SPRY domain is only reported as a functional domain in effectors of plant-parasitic nematodes, but not of other plant pathogens. SPRYSEC effectors have been implicated in both suppression and activation of plant immunity, but other possible roles in nematode virulence remain undefined. Here, we review the latest reports on the structure, function, and sequence diversity of SPRYSEC effectors, which provide support for a model featuring these effectors as a versatile protein-binding platform for the nematodes to target a wide range of host proteins during parasitism.